The answer to the problem of 12X plus 13 equals 9 is x equals -1/3.

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

4+2x-2x+1=13+6 Combine like terms. (4+1=5; 2x-2x=0; 13+6=19) 5=19 This problem has no solution.

20

13...... 9 plus 5 equals 14...... 14 minus 1 equals 13

The answer to the problem of 13 equals -4x plus 9 is x equals -1.

93+050+50-792+180+13and so on

(4 + 2x) - (-2x + 1) = 13 + 6 4 + 2x + 2x -1 = 19 4x +3 = 19 4x = 19 - 3 4x = 16 therefore x = 16/4 x = 4

13

No it doesn't. That sum is 100.

19

18 + 13= 31

1 plus 19 equals 20 2 plus 18 equals 20 3 plus 17 equals 20 4 plus 16 equals 20 5 plus 15 equals 20 6 plus 14 equals 20 7 plus 13 equals 20 8 plus 12 equals 20 9 plus 11 equals 20 10 plus 10 equals 20 1 times 20 equals 20 2 times 10 equals 20 4 times 5 equals 20

-1

1

A = 6

multiply everything by -1 to get -6+(-13)=? multiply by -1 6+13=? that's easy to figure out 6+13=19 now multiply by -1 again to put it back how it was -6+(-13)=-19 The reason is this: you are missing 6 items. You lose 13 more items. How many are you missing now? Now you're missing 19 items.

x equals -3, and y equals 1.

If 5x plus 3y equals 13, the x equals 2 and y equals 1. This is because 5x2=10 and 3x1=3, and 10+3=13.

(3, 2)

x=4

-14

y=4

The answer to the mathematical equation 13 plus 19 is 32.

1 + x + 2x = 20 So 1 + 3x = 20 so that 3x = 19 then x = 19/3 or 61/3